The Development of Public Policies to Address Non-communicable Diseases in the Caribbean Country of Barbados: The Importance of Problem Framing and Policy Entrepreneurs - Nigel Unwin; T. Alafia Samuels; Trevor Hassell; Ross C. Brownson; Cornelia Guell (Kerman University of Medical Sciences, 2017)
Background Government policy measures have a key role to play in the prevention and control of noncommunicable diseases (NCDs). The Caribbean, a middle-income region, has the highest per capita burden of NCDs in the Americas. Our aim was to examine policy development and implementation between the years 2000 and 2013 on NCD prevention and control in Barbados, and to investigate factors promoting, and hindering, success. Methods A qualitative case study design was used involving a structured policy document review and semistructured interviews with key informants, identified through stakeholder analysis and 'cascading.' Documents were abstracted into a standard form. Interviews were recorded, transcribed verbatim and underwent framework analysis, guided by the multiple streams framework (MSF). There were 25 key informants, from the Ministry of Health (MoH), other government Ministries, civil society organisations, and the private sector. Results A significant policy window opened between 2005 and 2007 in which new posts to address NCDs were created in the MoH, and a government supported multi-sectoral national NCD commission was established. Factors contributing to this government commitment and funding included a high level of awareness, throughout society, of the NCD burden, including media coverage of local research findings; the availability of policy recommendations by international bodies that could be adopted locally, notably the framework convention on tobacco control (FCTC); and the activities of local highly respected policy entrepreneurs with access to senior politicians, who were able to bring together political concern for the problem with potential policy solutions. However, factors were also identified that hindered multi-sectoral policy development in several areas, including around nutrition, physical activity, and alcohol. These included a lack of consensus (valence) on the nature of the problem, often framed as being predominantly one of individuals needing to take responsibility for their health rather than requiring government-led environmental changes; lack of appropriate detailed policy guidance for local adaptation; conflicts with other political priorities, such as production and export of alcohol, and political reluctance to use legislative and fiscal measures. Conclusion The study's findings indicate mechanisms to promote and support NCD policy development in the Caribbean and similar settings.